Lifetime Analysis on Centrifugal ID Fan Foundation in Cement Plants - Eskandari-Naddaf, Hamid; Gharouni-Nik, Morteza; Pakzad, Amir (International Journal of Integrated Engineering, 2018)
The dynamic behavior of centrifugal ID fan foundation of cement plants to perform the lifetime analysis was investigated in this study. To this end, a three-dimensional (3D) finite-element model (FEM) of this foundation was proposed and the analyses under static and dynamic loads for various modulus of elasticity of concrete (Ec= 20, 25, 28 and 30 GPa) and reinforcement (Es= 200, 250, 300 GPa) and rotor speeds of 400, 800, 1200, and 1800 rounds per minute (rpm) were conducted. The results show that the stress and deflection for a certain ID fan is around 2.5 and 10 times more under dynamic loading compared to static loading. Therefore, the excessive vibrations induced by increased speed of ID fan can result in reduced lifetime and fatigue of the foundation. Comparison of FEM results with laboratory-based evidence verified the accuracy of simulations made by the FEM. The proposed model can thus be applied to determine the critical points in foundation structure in order to obtain optimum results of design parameters.